SELF-CONTROL, INTEGRITY, AND PROFESSIONALISM: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT IN A STATE CORRECTIONAL INSTITUTION - Cahyono, Arif; Qomariah, Nurul; Herlambang, Toni (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
Kraksaan Class IIB Prison plays a strategic role in the correctional system, where employee professionalism is crucial for managing challenging and stressful tasks. This study aims to examine the influence of self-control and integrity on the professionalism of Kraksaan Class IIB Prison employees, both directly and indirectly through organizational commitment as a mediating variable. Self-control and integrity are considered fundamental factors in shaping employees’ organizational commitment, which in turn enhances professionalism in performing tasks within a dynamic and stressful environment. The research employs a quantitative approach, collecting data through questionnaires distributed to prison employees. Data analysis was conducted using Structural Equation Modeling (SEM) with WarpPLS statistical software to test the relationships between variables. The results indicate that self-control and integrity have a positive and significant effect on employee professionalism. Additionally, these two variables positively and significantly influence organizational commitment, which mediates their impact on professionalism. These findings underscore the importance of developing self-control, integrity, and organizational commitment as key strategies to improve the professionalism of Kraksaan Class IIB Prison employees.